Social Capital, Employee Personal Value, Job Performance, and Organizational Citizenship Behaviour: Case among Employees in Private Hospitals in West Jakarta - Cika, C.; Emilisa, Netania; Surbakti, Geby Gracela Surnina; Mumtazah, Kirana Ainayya (Manunggal Halim Jaya, 2026)
The purpose of this research is to explain the influence of Social Capital and Employee Personal Value on Job Performance with Organizational Citizenship Behavior as an intervening variable that in private hospital in West Jakarta. This research fills in the gap of previous fact-finding by investigating Social Capital and Employee Personal Value as a whole influencing variable which is mediated by Organizational Citizenship Behaviour toward Job Performance in private hospitals Indonesia. This work has a quantitative approach, offering a cross-sectional survey with 200 participants who were recruited by using the purposive sampling method (online questionnaires). Four established theoretical constructs were measured using a modified on five-point Likert scale making them suitable for Structural Equation Modeling (SEM) analysis. The findings suggest that all measurements indices are valid and reliable, and the full structural model has an acceptable fit. The results reveal that the Social Capital and Employee Personal Value have a positive and significant (p < 0.05) impact on both the OCB and Job Performance. Furthermore, Job Performance is enhanced by Organizational Citizenship Behavior as a mediator among Social Capital, Employee Personal Value and performance. These findings imply that in a working context with high trust psychological work contract and good mutual social network, warm personal worth attributes can facilitate extra-role behavior for superior performance. Practical implications:This study emphasizes the need to develop integration among chain of command, stronger implementation on positive employ values and supportive organizational culture in private hospital context.